Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1523/jneurosci.3263-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nigral Inhibition of GABAergic Neurons in Mouse Superior Colliculus

Abstract: The current dominant concept for the control of saccadic eye movements by the basal ganglia is that release from tonic GABAergic inhibition by the substantia nigra pars reticulata (SNr) triggers burst firings of intermediate gray layer (SGI) neurons in the superior colliculus (SC) to allow saccade initiation. This hypothesis is based on the assumption that SNr cells inhibit excitatory projection neurons in the SGI. Here we show that nigrotectal fibers are connected to local GABAergic neurons in the SGI with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 52 publications
0
62
0
Order By: Relevance
“…Since electrical activity in the SC is regulated by GABA (Chevalier et al, 1985; Chevalier and Deniau, 1990; Hall and Lee, 1993; Lee et al, 2001, 2007; Behan et al, 2002; Kaneda et al, 2008; Isa and Hall, 2009), we tested the actions of two GABA A receptor antagonists, bicuculline (50 μ m) and gabazine (SR95531, 5 μ m) (bicuculline and gabazine were used interchangeably and the results combined). These drugs generally increased the amplitude of optical signals, but had the greatest effects on after-depolarizations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since electrical activity in the SC is regulated by GABA (Chevalier et al, 1985; Chevalier and Deniau, 1990; Hall and Lee, 1993; Lee et al, 2001, 2007; Behan et al, 2002; Kaneda et al, 2008; Isa and Hall, 2009), we tested the actions of two GABA A receptor antagonists, bicuculline (50 μ m) and gabazine (SR95531, 5 μ m) (bicuculline and gabazine were used interchangeably and the results combined). These drugs generally increased the amplitude of optical signals, but had the greatest effects on after-depolarizations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the after-depolarization is shaped by GABA A receptor mediated inhibition and it is likely that prolonged bursting by GABAergic horizontal cells curtails prolonged bursting of narrow-field and wide-field vertical cells. Previous studies have shown enhanced excitatory responses in the SC following GABA A receptor blockade (Isa et al, 1998; Özen et al, 2000; Saito and Isa, 2003; Kaneda et al, 2008; Phongphanphanee et al, 2008). Our results are consistent with these results, but indicate that each temporal component of the optical signal is modulated by GABA A receptors differently.…”
Section: Discussionmentioning
confidence: 98%
“…8D) as in other species (54)(55)(56). Furthermore, the basal ganglia output nuclei instead provide tonic GABAergic inhibition to the tectal output cells in lamprey as well as in mammals (31,(57)(58)(59). This GABAergic input to the tectal output cells can serve to gate the circuit and allow activation through a temporary release from inhibition (disinhibition) (60).…”
Section: Discussionmentioning
confidence: 99%
“…This GABAergic input to the tectal output cells can serve to gate the circuit and allow activation through a temporary release from inhibition (disinhibition) (60). In rodents, it has also been shown that GABAergic neurons in the deep layer of tectum/colliculus are under nigral inhibition and that this inhibition is topographically organized in register (58,61). To what extent the basal ganglia influence processing in tectum by disinhibition of local GABAergic neurons is as yet not clear.…”
Section: Discussionmentioning
confidence: 99%
“…These models have argued that disinhibition of target nuclei is critical to movement, consistent with targeting of nigral projections to excitatory projection neurons in the colliculus (Jiang et al, 2003). However, a recent study has demonstrated that nigral projection neurons may also synapse on inhibitory neurons in the superior colliculus (Kaneda et al, 2008), thus complicating a simple disinhibition model (Basso and Sommer, 2011).…”
Section: Projections From the Substantia Nigra Pars Reticulatamentioning
confidence: 97%